Wheat Cost-Return Budget in Western Kansas - Dumler, Troy J.; O'Brien, Daniel M.; Olson, Brian L.S.; Martin, Kent L. (My University, 2009)
This publication projects a budget that reflects expected income and costs based on typical production of wheat in western Kansas.
MF903_2009_12
Keywords: MF917; Economics; Crops; MF